AQP1 Is Up-Regulated by Hypoxia and Leads to Increased Cell Water Permeability, Motility, and Migration in Neuroblastoma - Huo, Zihe; Lomora, Mihai; Kym, Urs; Palivan, Cornelia; Holland-Cunz, Stefan G.; Gros, Stephanie J. (Frontiers in Cell and Developmental Biology, 2021)
The water channel aquaporin 1 (AQP1) has been implicated in tumor progression and metastasis. It is hypothesized that AQP1 expression can facilitate the transmembrane water transport leading to changes in cell structure that promote migration. Its impact in neuroblastoma has not been addressed so far. The objectives of this study have been to determine whether AQP1 expression in neuroblastoma is dependent on hypoxia, to demonstrate whether AQP1 is functionally relevant for migration, and to further define AQP1-dependent properties of the migrating cells. This was determined by investigating the reaction of neuroblastoma cell lines, particularly SH-SY5Y, Kelly, SH-EP Tet-21/N and SK-N-BE(2)-M17 to hypoxia, quantitating the AQP1-related water permeability by stopped-flow spectroscopy, and studying the migration-related properties of the cells in a modified trans-well assay. We find that AQP1 expression in neuroblastoma cells is up-regulated by hypoxic conditions, and that increased AQP1 expression enabled the cells to form a phenotype which is associated with migratory properties and increased cell agility. This suggests that the hypoxic tumor microenvironment is the trigger for some tumor cells to transition to a migratory phenotype. We demonstrate that migrating tumor cell express elevated AQP1 levels and a hypoxic biochemical phenotype. Our experiments strongly suggest that elevated AQP1 might be a key driver in transitioning stable tumor cells to migrating tumor cells in a hypoxic microenvironment.